ANALYSIS OF THE APPLICATION OF ENTITY FINANCIAL ACCOUNTING STANDARDS WITHOUT PUBLIC ACCOUNTABILITY ABOUT EMPLOYEE BENEFITS WITH THE IMPORTANCE PERFORMANCE ANALYSIS METHOD - Nasution, Iqbal Reza; Riyadi, Sugeng (Jurnal Comparative: Ekonomi dan Bisnis, 2024)
This research aims to determine the application of SAK ETAP regarding employee benefits and the method for calculating SAK ETAP employee benefits in private companies in Jabodetabek as well as the impact of implementing the Job Creation Law on SAK ETAP calculating employee benefits using the Importance Performance Analysis method. The research methodology used in this research is descriptive quantitative. The population in this research are private companies in Jabodetabek. The sampling technique in this research used simple random sampling with a sample of 100 respondents. Analysis of this research data uses validity tests, reliability tests, and Importance Performance Analysis (IPA). The results of this research indicate that the implementation of SAK ETAP regarding employee benefits in private companies involves the process of recording, measuring and reporting employee benefits given to employees, the method for calculating SAK ETAP employee benefits in private companies is divided into 4 calculations, namely Short-Term Employee Benefits, Post-Employment Benefits, Other Long-Term Employee Benefits, and Severance Pay, as well as the impact of the implementation of the Job Creation Law on SAK ETAP for calculating Employee Benefits using the Importance Performance Analysis method. It can be concluded that company policies regarding employee benefits may change after the implementation of the Job Creation Law.